2018
DOI: 10.21577/0103-5053.20180236
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate Adsorption by Montmorillonites Modified with Lanthanum/Iron and a Laboratory Test using Water from the Jacarepaguá Lagoon (RJ, Brazil)

Abstract: Montmorillonites modified with lanthanum(III) and iron(III) were prepared from two commercial clays. These materials were characterized by powder X-ray diffraction analysis, X-ray fluorescence, infrared spectroscopy, N 2 adsorption, and scanning electron microscopy. The incorporation of lanthanum(III) and iron(III) varied from 0 to 4.00%. The amount of these cations governed the adsorption capacity of the material since an increase in the percentage of La by 1.7 times improved the adsorption capacity by 3.3 ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 46 publications
4
5
2
4
Order By: Relevance
“…The black clay soils CEC were (~20 meq/100g soil) higher than red clay soils. The observed clay soils CEC values were within the previously reported range (De Castro et al, 2019). NC was prepared through the ion exchange method described in Manocha et al (2008) and Shirsath et al (2011).…”
Section: Synthesis Procedures 221 Pnc Constituents Synthesissupporting
confidence: 74%
See 2 more Smart Citations
“…The black clay soils CEC were (~20 meq/100g soil) higher than red clay soils. The observed clay soils CEC values were within the previously reported range (De Castro et al, 2019). NC was prepared through the ion exchange method described in Manocha et al (2008) and Shirsath et al (2011).…”
Section: Synthesis Procedures 221 Pnc Constituents Synthesissupporting
confidence: 74%
“…Among the pollutants, P is the major nutrient for sustaining life on earth (Waweru et al, 2019) and the normal functioning of the ecosystem (Liu and Zhang, 2015). However, excess phosphate concentration of P as 0.02-0.39 mg P/L causes eutrophication, pollutes the water bodies, and 0.75-1.20 mg P/L is called hypereutrophic (De Castro et al, 2019;Yang et al, 2019). As a result, in most countries, recommended effluent phosphate concentrations were generally <2 mg P/L despite variation based on the receiving water bodies sensitivity: for example, European Union, directive 91/271/EE endorses 1-2 mg P/L of total phosphorus (TP) in the discharge effluent (Peleka and Deliyanni, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tian et al (2009) investigated the use of bentonite pillared with Al 3þ and mixtures of Al 3þ and La 3þ polyhydroxy cations, finding that the mixed systems provided higher adsorption capacities. de Castro et al (2018) investigated the intercalation of two montmorillonites with mixtures of La 3þ and Fe 3þ , stating that the use of Fe 3þ is economically advantageous since Fe 3þ salts are less expensive than La 3þ ones. However, modification with La 3þ renders materials that are not susceptible to redox reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The authors [54], for example, investigated and compared the effect of montmorillonite content in a natural Arabian clay with a bentonite, and the results showed that the natural clay presented 20.83 m 2 g -1 of surface area against 44.28 m 2 g -1 of bentonite surface area. Others authors [55] studied the modification of commercial montmorillonites with lanthanum (III) and iron (III), obtaining values of average pore size and pore volume in the range of 59.0 to 74 Å and 0.09 to 0.16 cm 3 g -1 , respectively.…”
Section: Resultsmentioning
confidence: 99%